BioWes-from design of experiment, through protocol to repository, control, standardization and back-tracking. Issue 1 (July 2016) - Cisar, Petr; Soloviov, Dmytro; Barta, Antonin; Urban, Jan; Stys, Dalibor
Abstract Background One of the main challenges in modern science is the amount of data produced by the experimental work; it is difficult to store, organize and share the scientific data and to extract the wealth of knowledge. Experimental method descriptions in scientific publications are often incomplete, which complicates experimental reproducibility. The proposed system was created in order to address these issues. It provides a solution for management of the experimental data and metadata to support the reproducibility. Implementation The system is implemented as a repository for experiment descriptions and experimental data. It has three main entry points: desktop application for protocol design and data processing, web interface dedicated for protocol and data management, and web-based interface for mobile devices suitable for the field experiments. The functionality of desktop client can be extended using the custom plug-ins for data extraction and data processing. The system provides several methods to support experimental reproducibility: standardized terminology support, data and metadata at a single location, standardized protocol design or protocol evolution. Results and discussion The system was tested in the framework of international infrastructure project AQUAEXCEL with five pilot installations at different institutes. The general testing in Tissue culture certified laboratory, Institute of complex systems and IFREMER verified the usability under different research infrastructures. The specific testing focused on the data processing modules and plug-ins demonstrated the modularity of the system for the specific conditions. The BioWes system represents experimental data as black box and therefore can handle any data type so as to provide broad usability for a variety of experiments and provide the data management infrastructure to improve the reproducibility and data sharing. Conclusions The proposed system provides the tools for standard data management operations and extends the support by the standardization possibilities, protocol evolution with visualization features and modularity based on the data processing modules and device communication plug-ins. The software can be used at different organization levels: from a single researcher (to improve data organization) to research consortium through the central protocols management repository. Support from the protocol design until being shared with the standardization features helps to improve the reproducibility of research work. The platform provides support from experimental protocol design to cooperation using simple sharing.